Efektifitas POC Rebung Bambu terhadap Tanaman Lobak (Rhapanus Sativus) - Febrialsa Ayudia Ekaputri; Dorkas Ina; Yusuf La’langan Limbongan; Sepsriyanti Kannapadang; Adewidar M. Pata’dungan; Willy Yavet Tandirerung (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
Organic agriculture plays a vital role in Indonesia’s agricultural development, with a key challenge being how to boost productivity efficiently and sustainably. Liquid Organic Fertilizer (LOF) derived from natural materials provides an eco-friendly option to improve soil fertility and crop yields. Bamboo shoots (Bambusa spp.), rich in organic carbon and gibberellin, present strong potential as LOF raw material to support plant growth. This study evaluated the effect of bamboo shoot-based LOF on the growth and yield of white radish (Raphanus sativus). The research was conducted from May to August 2025 in Kalolok, Batupapan Village, Tana Toraja Regency, South Sulawesi, at an altitude of 775 m. LOF was produced by fermenting 200 kg of ground bamboo shoots with 4 kg palm sugar, 1 liter EM4, and 200 liters water for 14 days. Treatments consisted of 0, 100, 200, and 300 ml per liter of water, applied twice at two-week intervals starting 14 days after planting. Using a randomized block design with four treatments and three replications, variables observed included plant height, leaf number, tuber size, and yield. Results showed that 300 ml/liter LOF gave the best outcomes: tallest plants (27 cm), most leaves (15.89), largest tubers (29.37 cm length; 6.06 cm diameter), and highest weight (731 g/plant; 6936.67 g/plot). These effects are linked to balanced nutrients (N, P, K, Mg, Ca) enhancing vegetative growth and tuber development. Thus, bamboo shoot-based LOF at 300 ml/liter is recommended as an effective organic fertilizer for white radish.